2011
DOI: 10.1029/2010ja015886
|View full text |Cite
|
Sign up to set email alerts
|

Superposed epoch analysis of magnetotail flux transport during substorms observed by THEMIS

Abstract: Cumulative magnetic flux transport earthward/tailward of the reconnection site in the plasma sheet or equatorward toward the neutral sheet (Φ) has been shown to be one of the most useful quantities for remotely sensing reconnection onset in the magnetotail. We examine the behavior of Φ during substorms near the onset meridian using superposed epoch analysis of Time History of Events and Macroscale Interactions during Substorms (THEMIS) probe observations at different downtail distances. Observational data come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 57 publications
5
33
0
Order By: Relevance
“…Figure 8a shows the time evolution of the duskward electric field, E Y , at the equator, which we evaluated using the relation E = −V × B. The large E Y region that appears at X ∼ −20 R E at t = −6 min propagates earthwards, which is consistent with the results of Liu et al (2011), who analysed the earthward-transported magnetic flux and found it to be proportional to the time integral of E Y . As expected, regions characterized by large E Y correlate well with significant earthward flows.…”
Section: Time Evolution In the Equatorial Regionsupporting
confidence: 73%
“…Figure 8a shows the time evolution of the duskward electric field, E Y , at the equator, which we evaluated using the relation E = −V × B. The large E Y region that appears at X ∼ −20 R E at t = −6 min propagates earthwards, which is consistent with the results of Liu et al (2011), who analysed the earthward-transported magnetic flux and found it to be proportional to the time integral of E Y . As expected, regions characterized by large E Y correlate well with significant earthward flows.…”
Section: Time Evolution In the Equatorial Regionsupporting
confidence: 73%
“…THEMIS, consisting of five satellites distributed in the magnetotail and a comprehensive network of ground-based imaging and magnetometers, has made great progress in establishing the timeline of events during substorms. Results appear to show that transport of magnetic flux (from reconnection) in the mid-magnetotail precedes auroral breakup (Liu et al 2011), extending previous statistical investigations (Miyashita et al 2009). The timing is consistent with tracking of distinct auroral features (streamers, or poleward boundary intensifications) which propagate equatorward with auroral breakup subsequently being observed (Nishimura et al 2010).…”
Section: Substormssupporting
confidence: 73%
“…At P2(THC), B Z turned negative (Figure 3h) as the flux transport started to increase (Figure 3j). Such signatures are expected with onset of reconnection [ Angelopoulos et al , 2009; Liu et al , 2010], and the reconnection site was located Earthward of the P2(THC) spacecraft based on the negative excursion in B Z . The sharp dipolarization at P3(THD) and P4(THE) in the near‐Earth tail started at around 0222 UT (Figure 3i), and flux transport at P4(THE) increased significantly (Figure 3j).…”
Section: Overviewmentioning
confidence: 98%
“…Figure 3j shows the cumulative magnetic flux transport from P2(THC) and P4(THE), which is obtained by integrating E Y . This parameter has been found to be a useful quantity to show the enhanced flux transport rate and to detect the onset of reconnection [ Angelopoulos et al , 2009; Liu et al , 2010]. We integrated the Y component of the − V × B electric field starting from 0200 UT.…”
Section: Overviewmentioning
confidence: 99%